2020
DOI: 10.1002/cpe.5707
|View full text |Cite
|
Sign up to set email alerts
|

Agent‐based modeling approach for group polarization behavior considering conformity and network relationship strength

Abstract: SummaryCurrently, group behaviors happen frequently with the development of network technology. As a typical social group behavior, group polarization has been attracted more and more academic attention due to its significant disturbance to public's daily lives. At present, the classic J‐A (proposed by Jager and Amblard) and D‐W (proposed by Deffuant and Weisbuch) models are used to analyze group polarization process. However, the main shortcomings existing in these models are that the individuals' psychology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Compared with the research of traditional group behavior, group behavior in online social networks has various forms and spread more widely. The research on group behavior mainly includes group behavior identification, 14,15 group behavior modeling and prediction, [16][17][18] social network retweeting behavior prediction. [19][20][21] An important content of behavior research is the spread characteristics of behavior.…”
Section: Related Workmentioning
confidence: 99%
“…Compared with the research of traditional group behavior, group behavior in online social networks has various forms and spread more widely. The research on group behavior mainly includes group behavior identification, 14,15 group behavior modeling and prediction, [16][17][18] social network retweeting behavior prediction. [19][20][21] An important content of behavior research is the spread characteristics of behavior.…”
Section: Related Workmentioning
confidence: 99%
“…ey found that extreme information results in segregation and had a limited effect on the population, while milder messages have better success and a cohesion effect. Zhang et al [33] integrated the influence factors such as conformity and network relationship strength into the polarization model, and the simulation results indicated that different information interaction modes had essential influence on group attitude polarization. However, in their study, the information propagation process of the polarization phenomenon was not considered.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Meanwhile, the evolution of opinions on different dimensions shows relevance under specific conditions. Zhang et al extended the factors such as conformity and relationship strength to the polarization model, and analyzed the main factors influencing group polarization. Chen et al considered the heterogeneity and dynamic consistency of individuals involved in the polarization of public opinion.…”
Section: Literature Reviewmentioning
confidence: 99%